Construction and evaluation of panel count model for road accident data / Wan Fairos Wan Yaacob - Wan Yaacob, Wan Fairos (Institute of Graduate Studies, UiTM, 2015)
This thesis presents the work on modelling road accident count in Malaysia through the development panel count model. This research is motivated by several factors. The first is the alarming phenomenon pertaining to the high rates of road accidents which has generated interest among researchers and policy makers to find ways and means to overcome this global issue. Secondly, the effect of adverse weather condition is known to affect road safety and although various intervention measures have been implemented, significant results have yet to be achieved. Hence, a better understanding of such phenomenon is essential to allow necessary measures to be taken to improve road safety. An extensive literature review was made to gain a better understanding on road accidents phenomenon and evolution of statistical model for count data. Through an extensive literature review, the gap was identified in the development of road accident models in Malaysian which overlooked the panel count models. Additionally, there is also the issue of potential bias in the panel count model estimator particularly with the issues of fixed effects estimator. Thus, the first research objective is to develop panel count model for road accidents data in Malaysia. The second objective is to evaluate the effect of panel size and time dimension on the estimator of panel count model using Monte Carlo simulation...